Using an implementation science framework to advance the science of nursing education. - Oermann, Marilyn H.; Reynolds, Staci S.; Granger, Bradi B. (Journal of Professional Nursing, 2022)
The process of adopting evidence-based educational practices and teaching methods has not been examined in nursing education. This article provides a framework for adopting educational evidence and designing studies in nursing education using an implementation science (IS) framework. The three phases for implementing evidence-based practices (development, translation, and sustainment) are used for this framework. Preparatory activities are needed before implementing a new educational practice or method, followed by identification of implementation strategies (e.g., training and support of faculty, strategies for communication and tips to remove barriers, guides for deciding on timing), assessing process and outcome measures, and plans for sustaining the new practice. A process map, examples of implementation processes, and sample research questions guide nurse educators in planning and conducting studies using an IS framework. Research has not examined the processes and strategies for applying evidence-based educational practices in nursing. Studies using an IS framework are needed to provide knowledge about how to move evidence into routine educational practices and implement more effective teaching methods. This article provides guidance for nurse educators to begin this research and suggests possible research questions. • Studies in nursing education using implementation science are needed. • Implementing educational evidence requires development, translation, and sustainment. • Implementation strategies include training, communication, and resources. • Understanding context is important in adopting educational evidence.